Improvement of the productive behavior of growing-finishing pigs by consumption of liquid yeast additive - Díaz-Plascencia, Daniel; Ordóñez-Baquera, Perla Lucía; Mancillas-Flores, Pablo Fidel; Gallegos-Jiménez, Juan Carlos; Villarreal-Balderrama, José Alfredo; Espinoza-Prieto, José Roberto; Martínez-Yáñez, Rosario (Ecosistemas y Recursos Agropecuarios, 2022)
It was evaluated an apple yeast liquid additive (ALL) on the productive performance of pigs in the growing-finishing stage. Four levels of additive per kg of feed were tested: 0 mL kg−1 (T1: control), 50 mL kg−1 (T2), 100 mL kg−1 (T3) and 150 mL kg−1. Were used 24 pigs with an average age of 30 d an average initial weight of 28.170 ± 3.6 kg−1.The variables evaluated were live weight (LW), daily feed intake (DFI), daily weight gain (DWG) and feed conversion (FC). A univariate analysis was performed to detect statistical differences between treatments using a α= 0.05 confidence level. T3 was better (P < 0.05) for LW, DFI, DWG and FC. It is concluded that the addition of 100 mL of ALL per kg of feed in the growing-finishing diet of pigs improves the productive response.